Localism, candidate selection and electoral preferences in ireland - the general-election of 1977 - Marsh, M (Economic & Social Studies, 1981)
Irish parties tend to choose parliamentary candidates who have strong local attachments. Party is known to be the dominant factor in electoral choice but many voters, particularly rural voters, are often said to prefer locally based representatives. Systematic evidence is provided to show how effectively parties consider such preferences in drawing up lists of candidates to contest Constituencies in rural Ireland. Most candidates are selected at constituency level but the Fianna Fail leadership imposed several in 1977, a move justified by national rather than local electoral considerations. The weight of local attachments in electoral preferences is assessed through an analysis of transfer patterns and it is suggested that the importance of localism, even on cross-party voting, may have been exaggerated.
Keywords: Economics; Sociology